Tales of mystery & imagination - Poe, Edgar Allan, 1809-1849.; Rackham, Arthur, 1867-1939 (New York : Portland House Illustrated Classics, 1987)
Presents an anthology of tales of horror and the supernatural.
Keywords: Horror tales, American; Children's stories, American; Horror stories; Short stories